PENGUATAN KEMAMPUAN SOSIAL PADA PENATAAN KAWASAN KUMUH PERKOTAAN (Studi Kasus Kelurahan Cigugur Tengah Cimahi) - Yudha P Heston; Ahmad Yusuf A (Diponegoro University, 2013)
The focus of this research is to measure and identify the factors that can enrichment social skills, both for the government and society in rearrangement urban slum with a case study in Kelurahan Cigugur Tengah Cimahi city. Research methodology is Participatory Research Appraisal (PRA), to ensure the active involvement of the people who became the subject group. Based on the results of the study, the researchers have concluded that the success of social assistance in rearrangement urban slums depend on increasing the capacity of governments and communities governansi. Increased capacity of government governance can be done by encouraging the Regional Executive, gave a commitment to establish priority areas for quality improvement of social areas. Forming a business unit area that has the task of improving the quality of social structuring slum. Increase the capacity of communities governance be done with the commitment of citizens, actively involved in decision-making, planning, implementation, maintenance, monitoring and improving the quality of social contribution in structuring slum priority.